Laparoscopic uterovaginal anastomosis in bicornuate uterus with cervical and vaginal aplasia - Munjal, Rachita; Sundaram, Meenakshi; Patel, Juhul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
The presence of Cervical and Vaginal Aplasia with bicornuate uterus is a very rare mullerian anomaly. Its true incidence is still unknown. The presence of functioning bicornuate uterus poses a great challenge for a gynecologist because a successful repair could restore normal menses and may preserve a patient’s fertility. Hence, we report a case of 14-year-old unmarried female, known case of Bicornuate uterus with cervical and vaginal aplasia with history of a rudimentary horn excision. On clinical and radiological evaluation, she was diagnosed with complete cervical and vaginal aplasia with haematometra in right cornua of uterus. She underwent vaginoplasty along with laparoscopic uterovaginal anastomosis in an innovative way. On follow-up, hysteroscopy showed a patent anastomosis, vagina was completely healed, and she was menstruating normally.